Research in Communication, Disability, and Sport - Cherney, James L. and Lindemann, Kurt and Hardin, Marie (Communication & Sport, 2015)
Explorations of the intersections of disability and sport have painted a multilayered picture of crucial aspects of communication including issues of gender, health, politics, and organizational tensions. Media-focused scholarship has identified different ways that sport articulates, perpetuates, and can challenge ableist views of disabled bodies. This article explores sites for additional communication research building on work on disability and sport from outside the communication and media studies field. The scholarship on disability and sport is explored around three themes: disability sport and rehabilitation discourse; disability metaphors and stereotypes; and sport, public controversy, and disability law. Possibilities for communication-focused work around each of these themes are also explored, and a case is made for the continued emphasis on integration of feminist, queer, and critical race theory into the study of discourse around disability and sport.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMTY3NDc5NTEzNTE0ODQ3